The Clinical Efficacy of Tiban Syrup as Adjuvant Treatment in Patients with COVID-19: A Randomized, Double-Blind Clinical Trial: The clinical efficacy of Tiban syrup on COVID-19 - Kamalinejad, Mohammad; Sarmadian, Hossein; Shokouhi, Farzaneh; Dadmehr, Majid; Bahrami, Mohsen; Dehnad, Afsaneh; Almasi-Hashiani, Amir; Solgi, Mohammad Saleh; Salehi, Mehdi; Kamalinejad, Fatemeh; Latifi, Seied Amirhossein (Iranian Journal of Pharmaceutical Sciences, 2021)
Since the outbreak of the COVID-19 pandemic, we have witnessed extensive morbidity and mortality worldwide. However, an appropriate pharmaceutical treatment has not yet been introduced for this disease, and finding a safe and effective treatment is still ongoing. This study aimed to evaluate the safety and efficacy of Tiban (Mocozift) syrup (an herbal product of Trachyspermum ammi (L.) Sprague (Ajwain) and Ziziphus jujuba Mill. (jujube)) in adult patients with COVID-19. Patients with laboratory-confirmed SARS-CoV-2 infection were enrolled and randomly assigned to receive either placebo or Tiban syrup 5 cc, three times a day for 14 days, in addition to standard medications of COVID-19. Improvement in clinical outcomes, including cough, fatigue, dyspnea, appetite, and the occurrence of in-hospital mortality, were recorded.A total of 50 patients completed the study. The mean age of the patients was 56.5 years. There were 21 (42%) male and 29 (58%) female patients. There was a significant reduction in dyspnea after taking medication (p=0.001). Patients’ appetite significantly increased in the Tiban group (p=0.001). Also, a significant decrease was observed in the severity of fatigue score in the Tiban group (p=0.001). Compared to the placebo group, an increase in appetite and a decrease in fatigue occurred earlier in the Tiban group.The findings of this study suggest that the combination therapy with Tiban syrup and conventional medicine can reduce severity of dyspnea and fatigue, while it can increase appetite in patients with mild to moderate COVID-19.